Pengaruh Remunerasi terhadap Motivasi Kerja Pegawai Rumah Sakit : Literatur Review - Revina Rahmadani; Diana Safitri; Budi Hartono (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Providing adequate remuneration is an important step in enhancing work motivation, which in turn can have a positive impact on hospital staff performance, enabling them to deliver quality services. This literature review aims to further explore the influence of remuneration and work motivation in the hospital environment. A total of 10 relevant articles were reviewed regarding the relationship between remuneration and work motivation in hospitals. The databases used for this search were Google Scholar, Science Direct, and Semantic Scholar. The keywords used were remuneration, motivation, and hospitals. The results were filtered using the PICO elements and the CRAAP method. The findings indicate that remuneration not only serves as a tool for motivation but also improves job satisfaction, which contributes to better performance. Hospitals need to adopt a holistic approach that includes fair remuneration, recognition of performance, and a supportive work environment to motivate employees, which indirectly enhances the quality of healthcare services.